Practical methods to identify seepage paths in dam abutments in semi-arid areas: The Mujib dam in Jordan - Al-Sheriadeh, Mohanned S.; Amayreh, Lubna K. (Frontiers in Built Environment, 2022)
Mujib dam in Jordan experienced high seepage in 2004 in the right abutment. Initial examination of the cause blamed rocks there and excluded the clay core hydro-fracturing. The problem later was resolved by grouting the right abutment heavily. This work believes the grouting quantity was excessive and can be minimized if seepage paths were identified. For this purpose, the excavation cut photos during construction were revisited, piezometric levels of wells drilled after the seepage event were examined, and the physio-chemical characteristics of seepage water were correlated to those in the reservoir. All those methods combined succeeded in finding the seepage paths and their percentage contribution to the total seepage volume. They found that three-fourths of the seepage water occurred through a small area circling the right abutment gallery stair shaft walls and suggested the remaining one-fourth can be stopped over time by sediment deposition on the reservoir floor. Therefore, the previously applied grouting volume was high. In conclusion, the methods used in this work can identify seepage probable paths and confine solutions to them.